2014
DOI: 10.1155/2014/520281
|View full text |Cite
|
Sign up to set email alerts
|

Thyroid Disorders and Chronic Kidney Disease

Abstract: Thyroid hormones play a very important role regulating metabolism, development, protein synthesis, and influencing other hormone functions. The two main hormones produced by the thyroid are triiodothyronine (T3) and thyroxine (T4). These hormones can also have significant impact on kidney disease so it is important to consider the physiological association of thyroid dysfunction in relation to chronic kidney disease (CKD). CKD has been known to affect the pituitary-thyroid axis and the peripheral metabolism of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
92
2
21

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 108 publications
(119 citation statements)
references
References 21 publications
4
92
2
21
Order By: Relevance
“…This finding agreed with Mohamed et al, who reported: "increased prevalence of thyroid goiter (0%-9%) in patients with CKD". [1] Our finding also agreed with Selma et al, who reported that diffuse goiter is frequently common in HD (p = .0001). They found the mean thyroid volume was significantly higher in HD group (18.88 ± 3.20 ml), comparing to the normal group.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…This finding agreed with Mohamed et al, who reported: "increased prevalence of thyroid goiter (0%-9%) in patients with CKD". [1] Our finding also agreed with Selma et al, who reported that diffuse goiter is frequently common in HD (p = .0001). They found the mean thyroid volume was significantly higher in HD group (18.88 ± 3.20 ml), comparing to the normal group.…”
Section: Discussionsupporting
confidence: 93%
“…It was observed these hormones increased after HD. [1] The present study was conducted to assess thyroid disorders in patients suffering from CRF undergoing HD. In the present study, the incidence of thyroid disorders was common in female more than male.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In a previous study from this laboratory, we observed significantly impaired kidney function of patients with overt hypothyroidism [33]. Although, hyperthyroidism is usually not associated with kidney disease but has been shown to accelerate an initiated disease [34]. Limitations of the present study were the relatively small sample size and that the anthropometric measurements were not recorded.…”
Section: Discussionmentioning
confidence: 71%
“…This study is done to simplify the importance of interactions between thyroid function and kidney disease. 5 The objective of this study was to study the thyroid dysfunction in patients of chronic kidney disease for the prevalence of subclinical hypothyroidism.…”
Section: Introductionmentioning
confidence: 99%